Using video-based technology in powerlifting sport to support referees' decision making - Michalopoulos, N.; Katsini, C.; Raptis, G. E. (Conference on Human Factors in Computing Systems - CHI EA '19 -, 2019)
Referees' decisions in sport games, which must be made in less than a second, have an impact on the games' outcome. The use of hardware and/or software solutions could contribute towards increased accuracy of referees' decisions. Application of such solutions can be expensive, especially in the case of less popular sports. In this respect, we propose and evaluate a video-based system for helping referees in powerlifting to make better decisions. Results reveal promising accuracy rates of the proposed system. This attempt is the first step towards supporting referees in the powerlifting domain and further elaboration of the proposed system is required to achieve higher decision-making accuracy.